The future of wireless networks architectures, protocols, and services - Guizani, Mohesen; Chen, Hsiao-Hwa; Wang, Chonggang 1974- (Wireless networks and mobile communications series, 2016)
The Future of Wireless Networks: Architectures, Protocols, and Services discusses the future of wireless networks, including the emerging network architectures, underlying protocols, services, and applications